Violations of antioxidant-prooxidant spleen index and ceruloplasmin content in serum during acute blood loss, complicated by ischemia-reperfusion of limb and the effectiveness of its correction with carbacetam - Iavorska, I. V. (Journal of Education, Health and Sport, 2021)
Antioxidant-prooxidant imbalance is one of the key mechanisms of acute blood loss and ischemic-reperfusion syndrome. Under these conditions, the level of ceruloplasmin (CP) plays an important role, enhancing antioxidant protection and promoting hematopoiesis, exhibiting ferrooxidase action. However, in this case, the state of antioxidant-prooxidant balance in the spleen and the content of CP in the serum is studied insufficiently, thus there is no data on the effectiveness of carbacetam, which revealed a pronounced protective effect on antioxidant protection of the spleen. Objective of research: to determine the dynamics of the antioxidant-prooxidant index of the spleen and the content of CP in the serum in acute blood loss complicated by ischemia-reperfusion of the limb, and to evaluate the effectiveness of carbacetam in correction of the identified disorders. Materials of the research and their discussion. 108 nonlinear male rats weighing 200–220 g were used in the experiments. All experiments were performed under thiopental-sodium anesthesia. In animals, limb ischemia-reperfusion and acute blood loss were modeled separately and in one of the groups these injuries were combined. In a separate group, the detected disorders were corrected with carbacetam. After 1 and 2 hours, as well as after 1, 7 and 14 days in the spleen of experimental animals was determined content of reagents to thiobarbituric acid and catalase activity, and according to these results the antioxidant-prooxidant index (API) was calculated and was determined the content of CP in serum. Results of the research and their discussion. Modeling of acute blood loss, complicated by ischemia-reperfusion of the limb, contributed to a decrease in the value of API in the spleen, which indicates a shift in antioxidant-prooxidation balance towards the dominance of prooxidant mechanisms. Under these conditions, the content of CP in the blood serum increases significantly, which on the one hand compensates the lack of antioxidant protection, on the other hand indicates on the activation of the mechanisms of the body’s systemic response to inflammation. The use of carbacetam helped to shift the antioxidant-prooxidant balance of the spleen towards the dominance of antioxidant mechanisms and to reduction of the CP content in the serum, which indicates on a pronounced antioxidant and anti-inflammatory effect of the drug, as well as its prospects in cases connected with hemic hypoxia and ischemia-reperfusion syndrome. Conclusions: Complication of acute blood loss by limb ischemia-reperfusion contributes to the shift of antioxidant-prooxidant balance of the spleen towards the dominance of prooxidant mechanisms with a simultaneous increase in the content of CP of serum. The use of carbacetam helps to increase the value of API and reduce the content of CP in the serum.